Penerapan A-DIVA Scale Terhadap Tingkat Keberhasilan Perawat Dalam Pemasangan Akses Intravena Pada Pasien Lansia Di Instalasi Gawat Darurat - Maryudella Afrida; Siti Na'imah (YAYASAN PENDIDIKAN MANDIRA CENDIKIA, 2026)
Background: Intravenous access placement is one of the most frequently performed nursing procedures in the Emergency Department. In older adults, age-related physiological changes such as fragile veins, reduced vascular elasticity, and vein collapse increase the risk of failed peripheral intravenous cannulation on the first attempt. Multiple insertion attempts may increase patient discomfort, prolong treatment time, and elevate the risk of complications including phlebitis. The Adult Difficult Intravenous Access (A-DIVA) Scale is a predictive tool developed to identify patients with difficult intravenous access and assist healthcare providers in selecting appropriate insertion strategies. Objective: To describe the implementation of the A-DIVA Scale in improving the success of intravenous access placement among older adults in the Emergency Department of RSUD Kota Yogyakarta. Methods: This descriptive observational study was conducted in the Emergency Department of RSUD Kota Yogyakarta between September and November 2023. Thirty nurses and midwives were recruited using total sampling. Data were collected through direct observation using the A-DIVA Scale and an observation sheet assessing intravenous insertion success. Data were analyzed using descriptive statistics and presented as frequencies and percentages. Results: The first-attempt success rate of intravenous access placement using the A-DIVA Scale reached 96.7% (29 successful procedures), while only one procedure (3.3%) failed. Most patients were classified as having a moderate risk of difficult intravenous access (A-DIVA score 2–3), accounting for 50.0% of the sample. Conclusion: The implementation of the A-DIVA Scale demonstrated a very high success rate in peripheral intravenous access placement among older adults. The instrument may serve as an effective screening tool to identify patients with difficult intravenous access, thereby improving procedural success and supporting patient safety in emergency care. Keywords: A-DIVA Scale; intravenous access; older adults; emergency department